Study of the Effect of the Earthworm (Aporrectodea molleri) Cutaneous Excreta on Bacterial Growth. (29th May 2021) - Yakkou, Lamia; Houida, Sofia; Raouane, Mohammed; Amghar, Souad; El Harti, Abdellatif
Abstract : The effect on the bacterial growth of Aporrectodea molleri cutaneous excreta has given very satisfactory results. The cutaneous excreta were obtained using the electrical stimulation technique, recently developed by our laboratory. This technique made it possible to collect the excreta in sufficient quantities while ruling out any possible interference with the chemical constituents of the soil. The effectiveness of cutaneous excreta, tested as culture media at different concentrations on bacterial growth, was justified not only by the high growth rates but also by the concentrations used, which were several times lower than those of the conventional medium (nutrient agar). Indeed, the maximum growth rate recorded by E. coli and P. fluorescens is, respectively, 1.32 times and 2.99 times greater than that observed on the conventional medium. These higher levels are obtained at optimal excretion concentrations which are, respectively, 8 times and 133.33 times lower than the concentration of the conventional medium. The efficacy interval that delimited the excretion concentrations tested covers 8 successive concentrations ranging from 0.0075% to 1% for P. fluorescens, while for E. coli, this interval covers only three concentrations ranging from 0.06% at 0.25%. The growth rates of P. fluorescens are always higher than those of E. coli . The higher efficiency of excretions on the growth of P. fluorescens shows that this strain is more suited to use these excretions as a source of nutrients and to react positively to the stimulation of growth. These results, obtained in vitro, prove that, in the natural environment, the production of lubricating and viscous cutaneous excretions does not only have the role of facilitating the movement and digging of galleries by earthworms but also of enriching the soil in nutrients and growth factors with high added values for the activation and development of plant growth-promoting bacteria essential for soil fertility.